Augmented reality visualization interface for biometric wireless sensor networks. - Claros, Debora; De-Haro, Mario; Domínguez, Miguel; De-Trazegnies-Otero, Carmen Lourdes; Urdiales-García, Amalia Cristina; Sandoval-Hernández, Francisco (Springer, Berlín, 2007)
Wireless sensor networks are being intensely used in health care environments to collect biometric signals from patients. This paper presents an augmented reality visual interface based on artificial markers intended to be used by medical staff, to monitor real time information from different kind of sensors attached to the patients in care centers in a fast and flexible way. The system can be applied for any kind of information source. In this work, it has been tested with temperature and humidity sensors.
Keywords: Sistemas de comunicaciones inalámbricos; Detectores; Biometría; Augmented Reality; Visualization interface; Biometric sensor network; Technology integration; Computer vision